Activity of older tourists: Understanding their participation in social tourism programs. (October 2017) - González, Elisa Alén; Sánchez, Nieves Losada; Vila, Trinidad Domínguez
A global demographic shift is leading to an increasing number of older citizens, particularly in the most developed regions, and social tourism is becoming growingly relevant throughout Europe, especially in Spain, where it has been successfully developed by the Institute for Elderly and Social Services (IMSERSO) programs. The aim of this study is to create a profile of older tourists according to the types of trips they make. It uses a multinomial logistic regression to rate older citizens according to their motivation, travel, and sociodemographic characteristics. Results show that older tourists prefer organized trips regardless of whether they travel on IMSERSO trips or any other type of package tour.